Endothelial dysfunction in arterial hypertension: focus on the combination of trandolapril and verapamil - V. I. Makolkin (Кардиоваскулярная терапия и профилактика)
The beneficial effects of the combination of trandolapril and verapamil (combined medication Tarka) on endothelial function in arterial hypertension (AH) are presented. Antihypertensive effectiveness of the medication is discussed, in particular, among AH patients with renal disease, other target organ pathology, and diabetic nephropathy.